Perlindungan Hukum Pekerja Migran Tak Berdokumen dibawah Konvensi PBB 1990 - Sion Sianipar (Jurnal Hukum Lex Generalis, 2026)
This study explores the legal protection received by undocumented Indonesian migrant workers, based on the 1990 UN Convention and the concept of state responsibility. The method used is a normative legal analysis with an approach to relevant laws and concepts. The research findings indicate that the 1990 UN Convention guarantees the fundamental rights of migrant workers through the principle of non-discrimination, but its protection remains quite limited due to weak law enforcement mechanisms and low levels of ratification by states. In addition, the protection provided by states faces challenges in the form of a lack of consular support and legal recognition in destination countries. Strengthening regulations at the national level, interstate diplomacy and increasing the effectiveness of consular.